Survival and arrhythmic risk among ischemic and non-ischemic heart failure patients with prophylactic implantable cardioverter defibrillator only therapy: A propensity score-matched analysis. (1st January 2019) - Briongos-Figuero, Sem; Estévez, Alvaro; Luisa Pérez, M.; Martínez-Ferrer, José B.; García, Enrique; Viñolas, Xavier; Arenal, Ángel; Alzueta, Javier; Basterra, Nuria; Rodríguez, Aníbal; Lozano, Ignacio; Muñoz-Aguilera, Roberto
Abstract: Background: Concerns about the efficacy of prophylactic ICD in non-ischemic cardiomyopathy (NICM) heart failure (HF) patients are still present. We aimed to assess whether survival and arrhythmic risk were different among ischemic cardiomyopathy (ICM) and NICM ICD-only patients, along with specific predictors for mortality. Methods: HF patients undergoing ICD-only implant were extracted from the nationwide multicenter UMBRELLA registry. Arrhythmic events were collected by remote monitoring and reviewed by a committee of experts. Results: 782 patients (556 ICM; 226 NICM) were recruited: mean ejection fraction of 26.6%; 83.4% in NYHA class II-III; mean QRS duration of 108.9 ms (only 14.9% with QRS > 130 ms). After 4.35 years of mean follow-up, all-cause mortality rate was 4.2%/year. In propensity-score (PS) analysis no survival differences between ICM and NICM subgroups appeared (mortality rates: 19.4% vs. 20%, p  = 0.375). Age (hazard ratio [HR] = 1.02, p  = 0.009), diabetes (HR = 2.61, p  ≤ 0.001), chronic obstructive pulmonary disease (HR = 2.13, p  = 0.002), and previous HF (HR = 2.28, p  = 0.027) correlated with increased mortality for the entire population, however atrial fibrillation (AF) (HR = 2.68, p = 0.002) and chronic kidney disease (HR = 3.74, p  ≤ 0.001) emerged as specific predictors in NICM patients. At follow-up, 134 patients (17.1%) were delivered a first appropriate ICD therapy (5.1%/year) without significant differences between ICM and NICM patients in the PS analysis (17.6% vs. 15.8%, p  = 0.968). ICD shocks were associated with a higher mortality (HR = 2.88, p  < 0.001) but longer detection windows (HR = 0.57, p  = 0.042) correlated with fewer appropriate therapies. Conclusions: Mortality and arrhythmia free survival is similar among ICM and NICM HF patients undergoing ICD-only implant for primary prevention strategy. Highlights: This is the first real-world registry analysing hard endpoints in prophylactic ICD-only HF patients with narrow QRS complex. A propensity-score analysis has never been performed in this clinical setting. All-cause death and arrhythmic risks were similar among ischemic and non-ischemic patients after four years of mean follow-up. The benefit in non-ischemic HF patients might be the same, so ICD therapy should not be restricted to ischemic patients. The decision to implant and ICD must be individualized in patients with more comorbidity.